FORMULASI, EVALUASI, DAN OPTIMASI MASKER GEL PEEL-OFF MINYAK PEPPERMINT DENGAN VARIASI HPMC K4M DAN CARBOPOL 940 MENGGUNAKAN DESAIN FAKTORIAL - Tania, Alinda; Pramesty, Andhina; Daniatiek, Sonata (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Facial skin requires protection from environmental pollutants and ultraviolet exposure that can cause premature aging, acne, and dryness. Peel-off gel masks are practical cosmetic preparations that moisturize, revitalize, and can be easily removed after use. Peppermint oil (Mentha piperita L.) has cooling, antibacterial, and antioxidant properties, making it beneficial for oily and acne-prone skin. This study aimed to formulate and optimize a peppermint oil peel-off gel mask using Hydroxypropyl Methylcellulose (HPMC) K4M and Carbopol 940 as gelling agents and to evaluate its physical properties. A factorial design was applied with four combinations of HPMC K4M (2–4%) and Carbopol 940 (0.5–1%). Physical evaluations included organoleptic properties, homogeneity, pH, adhesion, drying time, and viscosity. Data were analyzed using Stat-Ease 360 software version 22 to determine the optimum formula. Increasing gelling agent concentrations decreased pH but increased viscosity, adhesion, and drying time. The optimum predicted formula was obtained at 2.75% HPMC K4M and 0.9793% Carbopol 940, showing desirable physical characteristics. The peppermint oil peel-off gel mask formulated with HPMC K4M and Carbopol 940 met the physical quality requirements. Factorial design optimization proved effective in determining the ideal formulation composition for optimal mask performance.